Improving The Students’ Reading Comprehension Through the K-W-L Technique - Rochmah, Noviatul; Shunlin, Yang (Universitas Muhammadiyah Gresik, 2024)
The aim of this research is to investigate the effect of the KWL technique in improving students' reading comprehension skills. Data will be analyzed quantitatively and qualitatively. The results of the observation checklist, field notes, and questionnaires were used to analyze the results of the pre-test and post-test. The observation results in the form of percentages were that for the first meeting it was 36% (very bad), for the second meeting it was 53% (fair), for the third meeting it was 63% (fair), while for the last meeting it was 80% (very good). The second success criterion is that 75% of students are actively involved in the teaching and learning process. The researcher will provide several recommendations for English teachers, schools and for future researchers related to this research.